Penerapan target costing sebagai pengendalian biaya produksi pada Usaha Mie Bakso Ojo Lali di Kota Bitung - Moningka, Eugenia Trixie Jayanti; Wangkar, Anneke; Pinatik, Sherly (Yayasan Widyantara Nawasena Raharja, 2025)
Target costing is the most effective way to determine production costs. The company sets a target based on competitive market prices, allowing it to achieve the expected profit. This study set out to determine how to implement target costing as a control of production costs in the Ojo Lali Meatball Noodle business. Ojo Lali Meatball Noodle Business is a food production company located in Bitung Barat 1 Village, Maesa District, Bitung City. The results of the study are clear: after implementing target costing, the company calculated production costs at IDR 82,072,000 per month, while the target costing calculation showed IDR 73,539,000 per month. This has led to a significant increase in profits, rising from 25.6% to 33.3%.